Three-drug therapy versus two-drug therapy for management of patient-reported manifestations and quality of life in chronic obstructive pulmonary disease patients: A meta-analysis - Ganesh Narayan Sharma, Syed Aamir Ali, Birendra Shrivastav, Aleemuddin Naveed Mohd (Journal of Applied Pharmaceutical Science, 2020)
Patient-reported manifestations and quality of life (QoL) data for chronic obstructive pulmonary disease (COPD) drugs are sparse. This study compared three-drug therapy comprising inhaled corticosteroids (ICS), long-acting beta2 agonists (LABA), and long-acting muscarinic antagonists (LAMA) with two-drug therapy (ICS/LABA or LABA/ LAMA) in terms of patient-reported manifestations and QoL. Randomized controlled trials (RCTs) comparing three-drug therapy with two-drug therapy in COPD patients were searched through Pubmed and meta-analyzed. Efficacy endpoints included St George Respiratory Questionnaire (SGRQ) score, SGRQ responders, COPD assessment test (CAT) score, rescue drug use, rescue drug-free days, and adverse events resulting in drug cessation. Three-drug therapy showed improvement in SGRQ scores [mean difference (MD), −1.66; 95% confidence interval (CI), −2.09 to −1.23] and SGRQ responders [Odds Ratio (OR), 1.30; 95% CI, 1.18–1.44] compared to ICS/LABA dual therapy; and SGRQ scores (MD, −1.65; 95%CI, −2.31 to −0.99) and SGRQ responders (OR, 1.20; 95%CI, 1.08–1.34) compared to LABA/ LAMA dual therapy. Similarly, results with CAT scores, rescue medication use, percentage of rescue medication-free days, and adverse events resulting in drug cessation favored the three-drug therapy compared to the two-drug therapy. Three-drug therapy had improved SGRQ scores, CAT scores, reduced rescue medication use, and better QoL.
Keywords: COPD assessment test (CAT), adverse events, St George Respiratory Questionnaire (SGRQ), meta-analysis, rescue medication use.